2020
DOI: 10.22373/ekw.v6i2.7015
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Lactic Acid Bacteria on Boiler Chicken

Abstract: The aims of this research were to isolate lactic acid bacteria from broiler chicken. The main material was a chicken boiler aged 30 days. The identification of LAB was carried out based on isolation and identification of morphological, phenotypic, and biochemical characteristics. Thirteen LAB isolates were obtained and 5 selected LAB isolates were identified based on growth levels, pH, and lactic acid levels. Five selected LAB isolates were identified as Lactobacillus genus which has Gram-positive, negative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…BR 17 isolate was obtained from the isolation of lactic acid bacteria from broiler chicken meat (Mudawaroch et al, 2019) (Mudawaroch et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BR 17 isolate was obtained from the isolation of lactic acid bacteria from broiler chicken meat (Mudawaroch et al, 2019) (Mudawaroch et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported that lactic acid can have significant antimicrobial effects (Gao et al, 2019) Researchers have developed Lactic Acid Bacteria that can be used for food fermentation (Mathur et al, 2020) Most of the use of lactic acid bacteria for milk fermentation (Widyastuti, and Febrisiantosa, 2014) (Montet et al, 2014) (Soro-Yao et al, 2014) (Tsuda et al, 2012)and lactic acid bacteria as starter on the manufacture of fermented sausages (Franciosa et al, 2018) Lactic acid bacteria are found naturally in foodstuffs including chicken meat (Sakaridis et al, 2014) (Arief et al, 2015) succeeded in isolating LAB from beef as a probiotic. Lactic acid bacteria BR 12, BR 17, BR 11, BR 10, and BR 7 obtained from broiler chicken meat resulted in the growth of lactic acid bacteria with continuous growth with the highest lactic acid levels and the lowest pH of all Lactobacillus genes (Mudawaroch et al, 2020). BR 17 isolate is more efficient in using sucrose when compared to BR 12.…”
Section: Introductionmentioning
confidence: 99%
“…LAB have been used in the last decades for preservation techniques such as fermentation, pharmacological product, and even new antibiotics development. The antimicrobial substances they produce are responsible for it [4].…”
Section: Introductionmentioning
confidence: 99%